2023
DOI: 10.1002/advs.202303404
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the 3D Conformation of Hard‐Core Soft‐Shell Particles Adsorbed at a Fluid Interface

Abstract: The encapsulation of a rigid core within a soft polymeric shell allows obtaining composite colloidal particles that retain functional properties, e.g., optical or mechanical. At the same time, it favors their adsorption at fluid interfaces with a tunable interaction potential to realize tailored two‐dimensional (2D) materials. Although they have already been employed for 2D assembly, the conformation of single particles, which is essential to define the monolayer properties, has been largely inferred via indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…To date, the visualization of the 2D hexagonal structure of compressed and deformed microgels at fluid interfaces has been conducted by using the interface of sessile dispersion droplets, 49,53,54 different from the three-dimensionally compressed microgels in colloidal crystals. 55,56 However, the results of such analyses have been limited to observation conditions where the compression could not be controlled, that is, the structural changes of the individual microgels/microgel arrays packed at the interface during compression has not been well understood.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the visualization of the 2D hexagonal structure of compressed and deformed microgels at fluid interfaces has been conducted by using the interface of sessile dispersion droplets, 49,53,54 different from the three-dimensionally compressed microgels in colloidal crystals. 55,56 However, the results of such analyses have been limited to observation conditions where the compression could not be controlled, that is, the structural changes of the individual microgels/microgel arrays packed at the interface during compression has not been well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Microstructural analysis of monolayers prepared via fluid interface-assisted assembly typically relies on microscopy (atomic force and electron microscopy) and scattering (X-ray and light scattering). , The application of such techniques assumes the microstructure is conserved during transfer to a solid interface and subsequent drying, which might be untrue. Combining ex situ (i.e., after the deposition of the monolayer on the solid substrate) with in situ analysis revealed significant changes in the microstructure . This study covers only micron-sized core-shell NCs.…”
Section: Assembly Protocolsmentioning
confidence: 93%
“…Many core-softened (CS) approaches have been proposed to model these complex fluids, including ramp-like, square and ramp shoulders, exponential, Hertzian, multi-Hertzian, and Gaussian potentials. 33–42 For instance, in the work by Grillo and co-authors, 5 a Hertzian potential was employed to reproduce the distinct patterns observed in soft colloids at liquid–liquid interfaces. Interestingly, they found that a key ingredient to observe a large variety of micropatterns is to first immobilize two layers of colloids onto a solid substrate one after the other.…”
Section: Introductionmentioning
confidence: 99%